Recent Advances in Inorganic Electrochromic Materials from Synthesis to Applications: Critical Review on Functional Chemistry and Structure Engineering. Issue 7 (4th March 2022) - Li, Borui; Dang, Jie; Zhuang, Qianyu; Lv, Zepeng
Abstract: For the assembly of electrochromic devices (ECDs) with generally multilayer structures, supportive components usually are needed to be incorporated with EC materials. Herein, we reviewed several impressive methods to design and fabricate ECDs with high performance and versatility based on recent frontier research. The first part of the review is centered on the desirability and strengthening mechanism of nanostructured inorganic EC materials. The second part illustrates the recent advances in transparent conductors. We then summarize the demands and means to modify the formation of electrolytes for practicable ECDs. Moreover, efforts to increase the compatibility with the EC layer and ion capacity are delineated. At the end, the application prospects of inorganic ECDs are further explored, which offers a guideline for the industrialization process of ECDs. Abstract : This review focuses on the structural composition of inorganic electrochromic devices and summarizes the recent research progress of electrochromic full devices.